Deprivation and trends in blood pressure, cholesterol, body mass index and smoking among participants of a UK primary care-based cardiovascular risk factor screening programme: both narrowing and widening in cardiovascular risk factor inequalities. Issue 9 (8th February 2006) - Lyratzopoulos, G; Heller, R F; McElduff, P; Hanily, M; Lewis, P
Abstract : Objectives: To examine recent time trends in blood pressure (BP), total cholesterol, body mass index (BMI) and current smoking among people in the UK of different deprivation groups. Design: Repeatable survey. Setting: Primary care-based UK cardiovascular risk factor screening programme (58 Stockport general practices). Participants: 37 161 women and 33 977 men aged 35–60 years responding to a screening invitation and with a first screening episode during 1989–99. Results: There were significant decreasing trends in total cholesterol (−0.06 mmol/l/year, 95% confidence interval (CI) −0.07 to −0.06 for women, −0.07 mmol/l/year, 95% CI −0.07 to −0.06 for men), with a significantly faster drop in more deprived groups (−0.005 mmol/year/increasing deprivation group, 95% CI −0.01 to −0.001 for both sexes). There were decreasing trends in current smoking prevalence (odds ratio (OR) 0.97/year, 95% CI 0.96 to 0.97 for women, OR 0.96/year, 95% CI 0.95 to 0.96 for men) with a significantly slower drop in the more deprived groups (OR 1.01/year/increasing deprivation group, 95% CI 1.00 to 1.01 for both sexes). There were significant increasing trends in BMI (0.11 kg/m 2 /year in women, 95% CI 0.09 to 0.13, 0.10 kg/m 2 /year in men, 95% CI 0.08 to 0.11), with a significantly slower increase in the more deprived groups among men only (−0.02 kg/m 2 /year/increasing deprivation group, 95% CI −0.01 to −0.03). Inequality in BP narrowed among men but widened among women. Conclusion: Inequalities in risk factors between different deprivation groups may be both widening (smoking, BP in women) and narrowing (total cholesterol, BMI and BP in men). Given baseline inequalities in risk factors levels, these trends suggest that inequalities in cardiovascular disease are likely to persist in the future.